Pharmacoeconomic evaluation of the modern nasal corticosteroids for the allergic rhinitis treatment. - A. G. Zadorozhna; O. V. Makarenko (Medičnì Perspektivi, 2018)
The increase of allergic rhinitis incidence is an actual problem for industrial cities. The literature data on allergic rhinitis incidence in countries of Europe andUkrainewas analyzed. According to different authors, the allergic rhinitis is registered in 12-24% of the inhabitants of the Russian Federation, 26-40% - of the USA, 24-32% - of France, 16% – of the UK, and 19% – of Denmark. There were distinguished three main clinical forms of allergic rhinitis: light, moderate and heavy. General pharmacotherapy principles of the light and moderate forms of allergic rhinitis course are presented in the current article. There were indicated medicines for the first-line therapy of allergic rhinitis group "R01AD" - the medicines acting on the respiratory system, decongestants and other drugs for topical use in diseases of the nasal cavity, corticosteroids. The assortment of nasal corticosteroids is presented by mometasone (13 trade names), beclamethasone (2 trade names), fluticasone propionate (5 trade names). It is also shown that 95.6% of the nasal corticosteroids is imported from 9 countries, mainly fromIndiaandBelgium. The Ukrainian spray Forinex produced by Pharmac is the only representative among the R01AD group, but unfortunately, according to pricing range is not a drug of choice among nasal corticosteroids. The received data testify to the risk of inclusion of only imported drugs in the insurance list and the low replacement rate by the Ukrainian drug for treatment of the allergic rhinitis.